2016
DOI: 10.1007/s11999-015-4590-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Age or Surgical Approach Associated With Osteonecrosis in Patients With Developmental Dysplasia of the Hip? A Meta-analysis

Abstract: Background Osteonecrosis of the femoral head is a major complication that negatively impacts the clinical and radiographic long-term outcome after treatment of developmental hip dysplasia (DDH). There are conflicting results in the literature whether age at the time of closed or open reduction and a specific surgical approach are associated with osteonecrosis. Better understanding of the impact of age at reduction and surgical approach is important to reduce the risk of osteonecrosis in patients with DDH. Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 93 publications
8
57
0
1
Order By: Relevance
“…A meta-analysis by Novais et al, which comprised of 481 hips treated by closed reduction and 584 hips treated by open reduction, did not find any association between closed reduction undertaken before or after 12 months and avascular necrosis. 22 There was also no association between the type of surgical approach (anterior or medial approach) and avascular necrosis. In our study the incidence of avascular necrosis is 7.9% (7 out of 88 hips) and this is comparable to that reported in this meta-analysis (8%) (23) ( Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…A meta-analysis by Novais et al, which comprised of 481 hips treated by closed reduction and 584 hips treated by open reduction, did not find any association between closed reduction undertaken before or after 12 months and avascular necrosis. 22 There was also no association between the type of surgical approach (anterior or medial approach) and avascular necrosis. In our study the incidence of avascular necrosis is 7.9% (7 out of 88 hips) and this is comparable to that reported in this meta-analysis (8%) (23) ( Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Hence, early ultrasound screening using the Graf method in some countries is recommended to timely detect hip immaturity and pathologies and to provide the optimal approach [16]. Several studies reported older age at the time of CR showing a higher rate of complications or further corrective surgeries [5][6][7], while others not [8,9,17]. RAD in group III (older age) was found to be signi cantly high, compared with Group I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Although this procedure generally achieves satisfactory outcomes, CR procedure may also lead to a number of adverse complications, including iatrogenic avascular necrosis (AVN), re-dislocation and residual acetabular dysplasia (RAD), which might need further surgeries (FS) to address the problem. Previous studies reported that increased age at the time of CR predicted a higher rate of complications or further corrective surgeries [5][6][7], while others not [8,9]. Moreover, it still remains controversial whether CR or open reduction (OR) should be adopted for children approaching or older than 18 months at the time of rst diagnosis, especially for the severe dislocated cases.…”
Section: Introductionmentioning
confidence: 99%
“…Results of bracing studies may be obfuscated by including patients with reducible and irreducible dislocated hips, unstable or subluxable hips and dysplastic hips together, 11,13,14,25,62 and studies comparing operative management also often fail to clearly define the included patient population. 63 To attempt to identify best practice evidence in DDH management, the International Hip Dysplasia Institute (IHDI) initiated in 2010 an international, multicentre prospective study 64 of infants with the most severe form of DDHdislocated hips at rest. Infants diagnosed under 18 months of age with a dislocated hip at rest were enrolled at nine centres across North America, Europe and Australia.…”
Section: Treatment and Managementmentioning
confidence: 99%